Insulin Resistance and Markers of Inflammation in HIV-infected Ugandan Children in the CHAPAS-3 Trial. Issue 8 (August 2017) - Dirajlal-Fargo, Sahera; Musiime, Victor; Cook, Adrian; Mirembe, Grace; Kenny, Julia; Jiang, Ying; Debanne, Sara; Klein, Nigel; McComsey, Grace A.
Abstract : Background: Few studies have investigated metabolic complications in HIV-infected African children and their relation with inflammation. Methods: We compared baseline and changes in insulin resistance [homeostatic model assessment of insulin resistance (HOMA-IR)] and in markers of inflammation over 48 weeks, in a subset of antiretroviral therapy (ART)–naive Ugandan children from the Children with HIV in Africa-Pharmacokinetics and Adherence/Acceptability of Simple Antiretroviral Regimens trial randomized to zidovudine-, stavudine- or abacavir (ABC)–based regimen. Nonparametric methods were used to explore between-group and within-group differences, and multivariable analysis to assess associations of HOMA-IR. Results: One-hundred eighteen children were enrolled, and median age (interquartile range) was 2.8 years (1.7–4.3). Baseline median HOMA-IR (interquartile range) was 0.49 (0.38–1.07) and similar between the arms. At week 48, median relative changes in HOMA-IR were 14% (−29% to 97%) in the zidovudine arm, −1% (−30% to 69%) in the stavudine arm and 6% (−34% to 124%) in the ABC arm ( P ⩽ 0.03 for all the arms compared with baseline, but P = 0.90 for between-group differences). Several inflammation markers significantly decreased in all study arms; soluble CD14 increased on ABC and did not change in the other 2 arms. In multivariate analysis, only changes in soluble CD163 were positively associated with HOMA-IR changes. Conclusions: In ART-naive Ugandan children, HOMA-IR changed significantly after 48 weeks of ART and correlated with monocyte activation.